2017
DOI: 10.1155/2017/1020357
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ferritin Deletion Exacerbates β‐Amyloid‐Induced Neurotoxicity in Mice

Abstract: Mitochondrial ferritin (FtMt) is a mitochondrial iron storage protein which protects mitochondria from iron-induced oxidative damage. Our previous studies indicate that FtMt attenuates β-amyloid- and 6-hydroxydopamine-induced neurotoxicity in SH-SY5Y cells. To explore the protective effects of FtMt on β-amyloid-induced memory impairment and neuronal apoptosis and the mechanisms involved, 10-month-old wild-type and Ftmt knockout mice were infused intracerebroventricularly (ICV) with Aβ25–35 to establish an Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 46 publications
(56 reference statements)
1
50
0
Order By: Relevance
“…Nuclei were counterstained with DAPI. The number of TUNEL-DAPI positive cells was counted as described previously [19]. The counting area was located in the same position in all groups.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclei were counterstained with DAPI. The number of TUNEL-DAPI positive cells was counted as described previously [19]. The counting area was located in the same position in all groups.…”
Section: Methodsmentioning
confidence: 99%
“…The memory deficits and spatial learning of mice were examined using the Morris water maze as previously described [18,19]. The experimental apparatus (diameter = 120 cm, height = 50 cm) was divided into four quadrants, filled with water, and maintained at 25°C.…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…APP/PS mice exhibit typical Ad phenotypes, including the impairment of memory and hippocampal long-term potentiation (LTP), loss of pyramidal cells and accumulation of Aβ; however, these symptoms usually appear in mice at a late stage (>6 months of age) (4). Aβ injections induce neurotoxicity and this may be a novel method of inducing Ad in mice, enabling further research to be performed; cell death in mice with a typical Ad phenotype has been observed in a short period of time following injection of Aβ (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miR-107 expression is downregulated in the temporal cortical grey matter during the early phases of Ad (17,18). Furthermore, accumulation of Aβ in the brain serves an important role in the pathogenesis of Ad (6). It has been reported that miRNAs regulate multiple aspects of Ad development and progression, indicating that targeting miRNAs may be a novel strategy of treating Ad (15,16).…”
Section: Introductionmentioning
confidence: 99%